Uric acid and arterial stiffness in children and adolescents: Role of insulin resistance and blood pressure - Genovesi, Simonetta; Montelisciani, Laura; Viazzi, Francesca; Giussani, Marco; Lieti, Giulia; Patti, Ilenia; Orlando, Antonina; Antolini, Laura; Salvi, Paolo; Parati, Gianfranco (Frontiers in Cardiovascular Medicine, 2022)
Several studies describe the association between serum uric acid (SUA) and arterial stiffness in adults. Uric acid contributes through several mechanisms to the increase in blood pressure (BP) and adversely affects the insulin signaling pathway. Moreover, SUA predict the development of hypertension and insulin resistance up to type 2 diabetes. Early arterial stiffening, estimated in a by carotid-femoral pulse wave velocity (PWV), may already be present in pediatric age. Aim of our study was to investigate the relationship between SUA and PWV in a pediatric population and its interaction with insulin resistance and BP. In 322 children and adolescents (56.2% male, mean age 11.3 [SD 2.8] years), we measured weight, height, waist circumference, BP and PWV. We also assayed SUA and estimated glomerular filtration rate (eGFR) and calculated HOMA-index as a marker of insulin resistance. Simple and multiple regression analyses were performed to assess variables associated with PWV. Mediation models were applied to identify the direct and indirect effects of individual variables on PWV. On univariate analysis, age (p<0.001), waist circumference-to-height ratio (p=0.036), systolic and diastolic BP (SBP and DBP) z-score (p<0.001), heart rate (p=0.028), SUA (p=0.002), HOMA-index (p<0.001), and eGFR (p=0.014) were shown significantly associated with PWV. The multiple regression model showed that only age (p=0.028), SBP z-score (p=0.006), and heart rate (p=0.001) were significantly associated with PWV. The results were superimposable when the DBP z-score replaced the SBP z-score in the model. Mediation models showed that the effect of eGFR on PWV was fully mediated by SUA (p=0.015) and that the effect of SUA on PWV was totally mediated by HOMA-index (p<0.001). Both SUA (p<0.01) and HOMA-index (p<0.01) had a significant association with higher SBP (DBP) z-scores. The double mediation model including both BP and HOMA-index showed that the SUA effect on PWV was totally mediated by both variables (p=0.005, for HOMA-index, p=0.004, for SBP z-score and p=0.007, for combined effect). The results were superimposable when the DBP z-score replaced the SBP z-score in the model. In conclusion, insulin resistance and BP are both important mediators of the association between SUA and vascular stiffness in pediatric age.